Limited cross reactivity among arginine kinase allergens from mealworm and cricket edible insects. (15th March 2019) - Francis, F.; Doyen, V.; Debaugnies, F.; Mazzucchelli, G.; Caparros, R.; Alabi, T.; Blecker, C.; Haubruge, E.; Corazza, F.
Highlights: Edible insects are increasingly promoted as an efficient and sustainable food source. Even if allergy to insects by ingestion is recognized, only a few studies are actually available. Allergenicity of arginine kinase (AK) from mealworms and crickets is comparatively investigated. Whole insects and purified proteins sources show different allergenic reactions based on entomological staff sera. Low specific allergenicity to AK is discussed in relation to insect safety for human food. Abstract: Insects are seen as a solution to the increasing demand for protein sources for food. However, entomophagy has unfortunately been linked to allergic reactions in Europe with people with professional contacts. As mealworms ( Tenebrio molitor ) and crickets ( Acheta domesticus ) have recently become commercially available (both whole or in food formulation) in several European countries, this research assessed the cross allergenicity of arginine kinase (AK). Based on the collection of sera from a entomology laboratory staff, oven cooked insects but also purified AK fractions were tested. Immunoblotting against the protein extracts revealed different Immunoglobulin E reactivity of sera according to the insect target species: two bands (40 and 14 kDa) for crickets and a pattern including light responses at 17, 25 and 37 kDa for mealworms. Focusing on AK, low specific allergenicity was here illustrated and discussed in relation to the development of a safe edible insect consumption by humans.